2006
DOI: 10.1189/jlb.0106019
|View full text |Cite
|
Sign up to set email alerts
|

Differential kinase requirements in human and mouse Fc-gamma receptor phagocytosis and endocytosis

Abstract: Fc gamma receptors (FcgammaRs) contribute to the internalization of large and small immune complexes through phagocytosis and endocytosis, respectively. The molecular processes underlying these internalization mechanisms differ dramatically and have distinct outcomes in immune clearance and modulation of cell function. However, it is unclear how the same receptors (FcgammaR) binding to identical ligands (IgG) can elicit such distinct responses. We and others have shown that Syk kinase, Src-related tyrosine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 56 publications
2
72
0
Order By: Relevance
“…Syk inhibition with BAY 61-3606 did not reduce the detection of intracellular DENV E protein, indicating that Syk is dispensable for viral replication. This is in agreement with the report that Syk activation is not required for Fc receptor-mediated endocytosis (69).…”
Section: Ade-induced Syk Activation Is Dispensable For Denvsupporting
confidence: 83%
“…Syk inhibition with BAY 61-3606 did not reduce the detection of intracellular DENV E protein, indicating that Syk is dispensable for viral replication. This is in agreement with the report that Syk activation is not required for Fc receptor-mediated endocytosis (69).…”
Section: Ade-induced Syk Activation Is Dispensable For Denvsupporting
confidence: 83%
“…Indeed, human Ig preparations were also strongly inhibitory on phagocytosis. Previous studies have demonstrated that Fc␥RI (CD64), Fc␥RIIA (CD32A), and Fc␥RIIIA (CD16A) can mediate IgG-driven phagocytosis (31,36,37). With regard to the polymorphism of CD16A, previously reported to play a role in the clinical response of some patients to rituximab (38, 39), we did not detect a significant difference in binding or phagocytosis of target cells, using macrophages homozygous for valine or phenylalanine FIGURE 7.…”
Section: Discussionmentioning
confidence: 38%
“…The TCR is another receptor whose function is modulated by c-Cbl through the ubiquitination of the TCR-chain (74). Finally, c-Cbl was shown to down-modulate the phagocytic function mediated by Fc␥Rs (75,76). These examples illustrate the involvement of the ubiquitin ligase activity of c-Cbl in the down-regulation of various immunoreceptors.…”
Section: Discussionmentioning
confidence: 99%